2001
DOI: 10.1007/bf03162432
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency tunable EPR spectroscopy of Cr3+ in synthetic forsterite

Abstract: The electron paramagnetic resonance spectra of isolated and dimer impurity centers of trivalent chromium ions in the octahedral M1 sites in synthetic forsterite are studied in the frequency range of 65-90 GHz. The measurements are performed at 4.2 K in magnetic. field from -0.04 to 0.3 T. The zero-field splitting between spin doublets of the isolated Cr" ion A s = 66.7 GHz and between spin sublevels of the Cr-Cr" dimer A d! = 71.5 GHz and Ade = 73.0 GHz is measured directly at zero field. The analysis of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Therefore, there are some mechanisms favorable for the formation of the Ho3+-Ho 3 § dimers in forsterite during the process of crystal growth. We suppose [25] that these mechanisms resulting in charge compensation of heterovalent dissolution of h0lmium in forsterite are similar to those which are responsible for the formation of dimer centers of trivalent 3d ions in forsterite and bromides [16,[27][28][29]. In this case the formation of the associates [Ho3+-VMg-HO 3+] takes place (here VMg is a vacancy of Mg2+).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there are some mechanisms favorable for the formation of the Ho3+-Ho 3 § dimers in forsterite during the process of crystal growth. We suppose [25] that these mechanisms resulting in charge compensation of heterovalent dissolution of h0lmium in forsterite are similar to those which are responsible for the formation of dimer centers of trivalent 3d ions in forsterite and bromides [16,[27][28][29]. In this case the formation of the associates [Ho3+-VMg-HO 3+] takes place (here VMg is a vacancy of Mg2+).…”
Section: Discussionmentioning
confidence: 99%
“…Asa rule, these associates have zero effective formal charge in respect to the host lattice. There were observed, in particular, the associates formed by two Cr 3+ ions in the M1 sites with a Mg 2+ vacancy between them instead of three adjacent Mg 2+ ions located in the above mentioned quasi-one-dimensional chain of magnesium positions MI in forsterite [16]. ions in the MI or M2 sites, and A13+ in the tetrahedral site, the nearest one to the impurity Cr 3+ [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several Cr 3C centers were studied by EPR in detail at X-band 8 -10 and at frequencies 65-85 GHz. 11 EPR signals of Cr 2C were observed presumably at X-band. 12 To the best of our knowledge, there is only one publication 13 devoted to studying Cr 2C : Mg 2 SiO 4 by tunable, highfrequency EPR spectroscopy.…”
Section: Methodsmentioning
confidence: 96%
“…Experimental observations have revealed that trivalent chromium ions can exist not only in the isolated form but also as associates with magnesium vacancies [31,32]. Tetravalent chromium ions substitute for silicon ions in tetrahedral sites.…”
Section: Forsteritementioning
confidence: 99%